Patients’ admission scheduling techniques and approaches - Abdalkareem, Zahraa Adnan; Amir, A.; EhKan, P.; Al-Betar, MA (International Journal of Engineering and Technology, 2018)
The aspects of scheduling and optimization are quite prominent in assorted domains whereby the incoming inputs or different type of traffic is processed to the further stage. In traditional ways, there are different approaches including shortest job first, first come first serve, round robin, ranking based and many others by which the overall scoring of inputs is done. In this research manuscript, the scheduling of patients’ arrival is addressed that is directly associated with the scheduling of incoming patients to the specific ward or room where that patient is required to be admitted. This work presents assorted approaches for patients’ admission scheduling including heuristic and meta-heuristic as well as related perspectives.